2013 American Control Conference 2013
DOI: 10.1109/acc.2013.6580084
|View full text |Cite
|
Sign up to set email alerts
|

A tuning procedure for ARX-based MPC of multivariate processes

Abstract: Abstract-We present an optimization based tuning procedure with certain robustness properties for an offset free Model Predictive Controller (MPC). The MPC is designed for multivariate processes that can be represented by an ARX model. The stochastic model of the ARX model identified from inputoutput data is modified with an ARMA model designed as part of the MPC-design procedure to ensure offset-free control. The MPC is designed and implemented based on a state space model in innovation form. Expressions for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…Box constraints may be formulated for the sequence ofû k+j|k and ∆û k+j|k . The unconstrained MPC can be represented as the convex quadratic optimization problem with the solution given in Jørgensen et al [4] and a tuning algorithm based on this formulation is presented in Olesen et al [11,12].…”
Section: The Mpc Control Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Box constraints may be formulated for the sequence ofû k+j|k and ∆û k+j|k . The unconstrained MPC can be represented as the convex quadratic optimization problem with the solution given in Jørgensen et al [4] and a tuning algorithm based on this formulation is presented in Olesen et al [11,12].…”
Section: The Mpc Control Problemmentioning
confidence: 99%
“…One drawback from introducing integrating modes in the controller is that it leads to a deliberate model plant mismatch which complicates the tuning procedure. Through a number of recent publications, we have advocated for a methodology for offset free ARX based linear MPC that is simple to implement [2,4,3,12,5]. This methodology is based on estimation of linear MISO models by standard convex optimization tools, a simple noise model to ensure offset-free tracking and a state space system formulation in innovation form.…”
Section: Introductionmentioning
confidence: 99%
“…In [16] a tuning strategy is proposed for constrained multivariable MPC of uncertain plants based on particle swarm optimization techniques. In [17], an optimization based tuning procedure with certain robustness properties for an offset free MPC is presented for multivariable processes.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, in this work, the key performance indicator of the auto-tuning method is the output variance. The output variance is also considered in the tuning procedure of Huusom et al (2012) and Olesen et al (2013). In Tran et al (2013), Tran et al (2012) and Ozkan et al (2012), it is shown that in the presence of model-plant mismatch and measurement noise, there ex-ists an optimal closed-loop bandwidth which corresponds to the minimum output variance.…”
Section: Introductionmentioning
confidence: 99%